Masquerading as pea plants: behavioural and morphological evidence for mimicry of multiple models in an Australian orchid - Scaccabarozzi, Daniela; Cozzolino, S.; Guzzetti, L.; Galimberti, A.; Milne, Lynne; Dixon, Kingsley; Phillips, R.D. (OXFORD UNIV PRESS, 2018)
Background and Aims: While there is increasing recognition of Batesian floral mimicry in plants, there are few confirmed cases where mimicry involves more than one model species. Here, we test for pollination by mimicry in Diuris (Orchidaceae), a genus hypothesized to attract pollinators via mimicry of a range of co-occurring pea plants (Faboideae). Methods: Observations of pollinator behaviour were made for Diuris brumalis using arrays of orchid flowers. An analysis of floral traits in the co-flowering community and spectral reflectance measurements were undertaken to test if Di. brumalis and the pea plants showed strong similarity and were likely to be perceived as the same by bees. Pollen removal and fruit-set were recorded at 18 sites over two years to test if fitness of Di. brumalis increased with the abundance of the model species. Key Results: Diuris brumalis shares the pollinator species Trichococolletes capillosus and T. leucogenys (Hymenoptera: Colletidae) with co-flowering Faboideae from the genus Daviesia. On Di. brumalis, Trichocolletes exhibited the same stereotyped food-foraging and mate-patrolling behaviour that they exhibit on Daviesia. Diuris and pea plants showed strong morphological similarity compared to the co-flowering plant community, while the spectral reflectance of Diuris was similar to that of Daviesia spp. Fruit-set and pollen removal of Di. brumalis was highest at sites with a greater number of Daviesia flowers. Conclusions: Diuris brumalis is pollinated by mimicry of co-occurring congeneric Faboideae species. Evidence for mimicry of multiple models, all of which share pollinator species, suggests that this may represent a guild mimicry system. Interestingly, Di. brumalis belongs to a complex of species with similar floral traits, suggesting that this represents a useful system for investigating speciation in lineages that employ mimicry of food plants.